CASH CONVERSION CYCLE AND PROFITABILITY FOOD AND BEVERAGE COMPANIES IN INDONESIA - Keti Purnamasari; Purwati Purwati; Gusti Ayu Oka Windarti; Elisa Elisa (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2023)
One measure used to measure the efficiency of working capital is Cash Conversion Cycle (CCC). The cash conversion cycle is a cycle that describes the length of time it takes a company to convert inventory and receivables into cash and pay debts. The lower the cash conversion cycle, the better. This study aims to analyze the relationship between the cash conversion cycle and profitability. The samples in this study were 17 food and beverage companies listed on the Indonesia Stock Exchange for the 2018 to 2022. This research found that there is a negative relationship between the cash conversion cycle and profitability as measured by Return on Assets and Return on Equity. The shorter the inventory conversion period and the receivables collection period and the longer the debt repayment period, the less cash conversion cycle can be. Reduced or lower cash conversion cycles indicate that the company has been able to optimize the use of its working capital so as to increase profitability.